Rishi coffins and the funerary culture of second intermediate period Egypt - Miniaci, Gianluca (GHP Egyptology, 2011)
"This volume is the first in-depth study of Egyptian Second Intermediate Period rishi coffins. It includes a catalogue of all published and many unpublished rishi coffins and its innovative analysis provides an entirely new evaluation of the funerary culture of the period based on the proposed typology of rishi coffins. The illustrated catalogue provides photographs for most of the coffins, including all examples stored in the Egyptian Museum of Cairo and unpublished material from Winlock's excavations in Thebes. This fundamental study will be for many years to come an essential contribution to the funerary culture of Egypt in one of the most important historical turning-points, the Seventeenth Dynasty and reunification under the early Eighteenth Dynasty." --Publisher's description.